The WTO at ten : the contribution of the dispute settlement system - Sacerdoti, Giorgio (CUP CambridgeGB)
Presents a critical assessment of the WTO and, in particular, its dispute settlement system after ten years of existence. Examines the relationship between trade negotiations and dispute settlement and seeks to respond to the question of what is the proper balance between political governance and judicialization. Focuses on the Appellate body and its contribution to the development of international trade law. Presents a comparative discussion of treaty interpretation by various international tribunals.